2011
DOI: 10.3109/02652048.2011.642016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of niosomes containing autoclavedLeishmania major: a preliminary study

Abstract: In this study, different positively charged niosomal formulations containing sorbitan esters, cholesterol and cetyl trimethyl ammonium bromide were prepared by film hydration method for the entrapment of autoclaved Leishmania major (ALM). Size distribution pattern and stability of niosomes were investigated by laser light scattering method and ALM encapsulation per cent was measured by the bicinchoninic acid method. Finally, the selected formulation was used for the induction of the immune response against cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…We have observed that the amount and the chain length of the ionic surfactants, play a key role in modifying the arrangements of the bilayer . Charged surfactants in the bilayer lead to increase in the curvature, thereby altering the size of the vesicles . The change in the size of the niosome leads to change in the area of the vesicular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that the amount and the chain length of the ionic surfactants, play a key role in modifying the arrangements of the bilayer . Charged surfactants in the bilayer lead to increase in the curvature, thereby altering the size of the vesicles . The change in the size of the niosome leads to change in the area of the vesicular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Niosomal sodium stibogluconate was shown to be more effective than liposomal vesicular formulations and free drug against experimental murine visceral leishmaniasis [73,96]. More recently, in vivo studies demonstrated that the niosomes containing autoclaved L. major have a significant result in the prevention of cutaneous leishmaniasis in BALB/c mice [97]. Furthermore, vaccination of C57BL/10 mice specifies that subcutaneous vaccination against cutaneous leishmaniasis with purified gp63 entrapped into niosomes, encouraged considerable resistance to this disease [98].…”
Section: Current Antileishmanial Drug-delivery Systemsmentioning
confidence: 97%
“…The gelation was considered successful, if the samples did not flow under gravity when the vials were inverted. [28,29] The CGC was found to be 18% (w/w) and 20% (w/w) for MO and GO, respectively. The MO gels containing 18% (w/w) SM were not stable after one month of storage at RT.…”
Section: Antimicrobial Studiesmentioning
confidence: 98%